PENGARUH JENIS BURUNG PUYUH (Coturnix-coturnix japonica) DENGAN PEMBERIAN PAKAN KOMERSIAL YANG BERBEDA TERHADAP PENAMPILAN PRODUKSI PERIODE BERTELUR - Dionysius Mone; Edhy Sudjarwo; Muharlien Muharlien (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2016)
The purpose of research was to determine effect quail type and different commercial feed on feed consumption, feed conversion, quail (Cortunix cortunix japonica) Hen Day Production (HDP). The material used for research were 48 heads bangkok quail and 48 heads bangkok-local quail (39 days of age). Method used in the research was experimental design. The data were analysed by Completely Randomize Design (RAL) by factorial design (2x3). The treatment consisted of two combination factor A1 (bangkok) and A2 (Bangkok-Local Crossbreed). The commercial feed consist B1, B2, and B3. The data were analyzed by ANOVA (analysis of variance) and Duncan Multiple Range Test. The result showed that the commercial feed different give a significant influence (P0.05) on feed conversion and HDP. The commercial feed different on feed conversion B1 were (3.96±0.03) B2 (5.35±0.20), and B3 (5,05±0,37). The commercial feed different on hen day production B1 were (64.52±3.08 %) B2 (51.24±0.09 %), and B3 (50.19±4.43 %). The interaction between quail A2 by commercial feeding with B1 feed conversion were (3.82±0.66), and HDP (68.71±13.54 %). Research concluded Bangkok-Local Crossbreed quail feeding by commercial feed A1 reduce feed conversion and improve hen day production (HDP). Keywords: Bangkok quail, Crossbreed quail, commercial feed, feed consumption, feed conversion, Hen Day Production (HDP).